Annular finite-time H∞ control of switched fuzzy systems: A switching dynamic event-triggered control approach. (August 2021) - Sun, Xue; Yang, Dong; Zong, Guangdeng
Abstract: This paper addresses the annular finite-time boundedness H ∞ control problem for a class of switched fuzzy systems. A novel switching dynamic event-triggered mechanism is proposed to save communication resources; where two different internal variables are designed and change according to a switching manifold. It is proved that the proposed switching dynamic event-triggered mechanism has a larger minimal inter-execution time in comparison with the static one. With a Lyapunov-like function including the internal dynamic variable, a criterion is established to ensure the annular finite-time boundedness H ∞ performance. A dynamic event-triggered controller and a set of feasible mode-dependent average dwell time switching signals are co-designed to achieve desired performance. Finally, an example is presented to validate the effectiveness of the proposed method.